Molecular genetic markers of breast cancer: current advances in understanding the etiology, prognostic value, and therapeutic opportunities - M. M. Omarov; V. V. Trusova; L. M. Agabekyan; I. R. Gaziev; Z. M. Alibekova; L. A. Aivazyan; E. A. Safarova; A. M. Adzhigulova; A. A. Darmilova; E. K. Khanmukhometova; I. R. Vanova; V. I. Pigareva (Акушерство, гинекология и репродукция)
Introduction. Breast cancer (BC) is the most common oncology pathology that holds a leading place among the causes of cancer death. Early diagnosis is critically important for successful treatment. Current molecular genetic research has revolutionized oncology allowing to classify breast cancer into various subtypes and, thereby, radically changing the approach to therapy.Aim: to analyze the literature data on up-to-date information regarding the molecular genetic BC markers and the prospects of their use for BC diagnostics and treatment.Materials and Methods. In accordance with the PRISMA guidelines, a systematic search was conducted in the PubMed/MEDLINE, eLibrary, and Google Scholar databases using Russian and English keywords: «breast cancer», «early breast cancer», «molecular markers of tumor cells», «chemotherapy», «hormone therapy», «estrogen and progesterone receptors», «triple-negative breast cancer», «neoadjuvant chemotherapy», «complete pathological response», «immunohistochemistry». Peer-reviewed publications in Russian or English containing original data on BC molecular diagnostics were included, with total of 39 publications selected for analysis.Results. High diagnostic and prognostic value was found for mutations in the BRCA1/2, PIK3CA,TP53, CHEK2, PALB2, and ESR1 genes, as well as for the expression of PD-L1, TILs (tumor-infiltrating lymphocytes), and Foxp3+ regulatory T cell levels. Modern technologies such as liquid biopsy, analysis of circulating tumor cells, and circulating tumor DNA allow for real-time tumor molecular profiling. This markedly expands the potential for personalized treatment strategies. HER-2-low subtype and ESR1 mutations require individualized therapeutic approaches.Conclusion. BC molecular markers have become a cornerstone for accurate diagnosis, risk stratification, and personalized therapy. Despite substantial research advances, the accessibility of molecular diagnostics, standardization of procedures, and integration of innovative technologies into clinical practice remain pressing issues. Systemic support is needed to implement molecular techniques into standard care protocols and ensure their broader application in real-world oncology settings.